PENGARUH KUALITAS PELAYANAN DAN SEMANGAT KERJA PEGAWAI TERHADAP KEPUASAN MASYARAKAT - Nopra Disti; Ratnawili Ratnawili (Yayasan Insani Mandiri Santani, 2020)
This study aim to determine the effect of service quality and employee morale on community satisfaction in Kaur Distric (case study on the of the Padang Guci Downstream District Office). This study usesa sample of 99 responden who us accidental sampling technigue. Data collection technique using quistionsnaires. Data analysis technique used are multiple liniar regression. This research usese validity test,realitytest,classic assumption test,reality test,classicassumption test followed by hipotesis testing.Based on result of multiple regressionanalysis’ service quality X1 and employee morale X2 have a signifikan effect on community satisfaction Ythis is evidecent by the regression equation Y = 5,124 + 0,981 X 1 + 1,860 X2 an the coefficien of determination R2 = 0,797 which means service quality X1 and employee morale X2 contribute to influence as much of 79,2 % on community satisfaction Y and 20,8 % are influenced by other factor not explained in the research. From the reserch partial hyphotesis testing (t test) it canbe seen that the variable service quality X1. employee morale X2 has a value of t count 5,910 and 0,000 < 0,05 this it can be concluded that the service quality X1 and employee morale X2 have a significant effection public satisfaction Y. From the result simultaneosly ( test t) can be know F count of 0,000 < 0,05 . This Ha accepteed Ho rejected. This meantthat together the quality of service and employee morale influence community satisfaction in the service of the Padang Guci sub-Distict Downsteam of Kaur District